Effect of antioxidant grafted graphene oxides on the mechanical and thermal properties of polyketone composites - Lim, Min-Young; Oh, Jinwoo; Kim, Hee Joong; Kim, Ka Young; Lee, Sang-Soo; Lee, Jong-Chan (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Polyketone (PK) composites were prepared by a polymer powder coating method using carbon nanomaterials, such as carbon nanotube (CNT), graphene oxide (GO), and antioxidant grafted GOs as filler materials. The antioxidant grafted GOs were obtained by grafting hindered amine and hindered phenol, respectively, onto the surface of the GOs. The PK composites containing the carbon nanomaterials showed much improved thermal stabilities and mechanical properties compared to PK. In particular, we found that the antioxidant grafted GOs are more effective in increasing the thermal properties of PK than CNT and GO without any antioxidant moieties. The enhanced thermal stability and mechanical property by the antioxidant grafted GOs can be explained by the combined antioxidant ability of the antioxidant functional groups and the rigid conjugated carbon units in the GOs having the ultrathin sheet shapes. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: CARBON NANOTUBES; ALIPHATIC POLYKETONES; NANOCOMPOSITES; POLYETHYLENE; MONOXIDE; DEGRADATION; TEMPERATURE; STABILITY; FUNCTIONALIZATION; POLYMERIZATION